2008
DOI: 10.1074/jbc.m705904200
|View full text |Cite
|
Sign up to set email alerts
|

Hsp60 Regulation of Tumor Cell Apoptosis

Abstract: Molecular chaperones may promote cell survival, but how this process is regulated, especially in cancer, is not well understood. Using high throughput proteomics screening, we identified the cell cycle regulator and apoptosis inhibitor survivin as a novel protein associated with the molecular chaperone Hsp60. Acute ablation of Hsp60 by small interfering RNA destabilizes the mitochondrial pool of survivin, induces mitochondrial dysfunction, and activates caspase-dependent apoptosis. This response involves disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
241
2
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(264 citation statements)
references
References 44 publications
18
241
2
3
Order By: Relevance
“…It has already been reported that Hsp60 has a pro-apoptotic role favoring activation of Caspase-3 (C3) [10,47] but others claim that Hsp60 is cytoprotective because it stabilizes the levels of survivin and inhibits p53, thus keeping the cell alive [9]. It is also known that Hsp60 forms a stable complex with pro-Caspase-3 (pC3) with the consequent anti-apoptotic effect [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been reported that Hsp60 has a pro-apoptotic role favoring activation of Caspase-3 (C3) [10,47] but others claim that Hsp60 is cytoprotective because it stabilizes the levels of survivin and inhibits p53, thus keeping the cell alive [9]. It is also known that Hsp60 forms a stable complex with pro-Caspase-3 (pC3) with the consequent anti-apoptotic effect [5].…”
Section: Discussionmentioning
confidence: 99%
“…Hsp60 has been implicated in carcinogenesis via its interaction with components of the Caspase cascade that leads to apoptosis. However, opinions about the role of this chaperone in carcinogenesis, and in apoptosis in particular, differ and it is not yet clear when and how Hsp60 is pro-apoptotic (i.e., it acts as an anti-cancer factor) or the contrary, namely it works in favor of the tumor by interfering with apoptosis [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Various data have revealed the need for Hsp60 by some types of tumor cells for their survival and growth. For example, elevated levels of this chaperonin in tumor cells have been linked to the ability to survive apoptotic stimuli, loss of RS, uncontrolled proliferation, and neoplastic transformation [51]. In our experimental model, decreased levels of Hsp60 were associated with appearance of senescence features and tumor-cell growth arrest, which coincided with Hsp60 modification such as hyperacetylation and ubiquitination.…”
Section: Discussionmentioning
confidence: 70%
“…Hsp60 is preeminently a protein-folding machine but it can also stimulate anti-apoptotic mechanisms involving sequestration of Bax-containing complexes thus favoring tumor cell survival [51,55]. However, it has been demonstrated that Hsp60 modified with Olinked N-acetylglucosamine (O-GlcNAcylation) in pancreatic bcells, under hyperglycemic conditions, shows a decreased interaction with Bax leading to cell death [56].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the phosphorylation of Hsp90 is known to regulate its chaperone function and hence its role in cell signaling (Mollapour et al, 2010). In addition, the expression levels of Hsps also vary in cancer and normal cells (Ghosh et al, 2008).…”
mentioning
confidence: 99%